Analisis Yuridis Pengampunan Pajak dalam Investasi di Indonesia - Agus Iskandar (Universitas Bandar Lampung (UBL), 2017)
Tax incentives, whether tax exemptions, tax breaks, accelerated depreciation and so are different from